Implementasi Lesson Study pada Mata Kuliah Pemahaman Lintas Budaya antara Universitas Negeri Semarang dan Universitas Pendidikan Ganesha - Andy Moorad Oesman; Yanuar Lutfi Rohman; Ai Sumirah Setiawati (IZUMI, 2026)
This study aims to evaluate the perceived effectiveness and implementation dynamics of Lesson Study in the Cross-Cultural Understanding course (Ibunka Rikai) conducted through the Merdeka Belajar Kampus Merdeka (MBKM) program. This descriptive qualitative research involved students and lecturers from Semarang State University and Ganesha University of Education. Data were collected through observations, in-depth interviews, and documentation, and analyzed using thematic analysis. The results highlight three main themes: (1) Improved quality of instructional design collaboration, (2) Dynamics of cross-cultural interaction in virtual spaces, and (3) Technical challenges and pedagogical adaptation. Findings indicate that while conventional methods often limit active interaction, the Lesson Study approach successfully facilitated deeper student engagement and understanding of Japanese cultural nuances. This study recommends integrating more stable infrastructure to support the sustainability of online Lesson Study. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor